LEGAL ANALYSIS OF ACCESS OF CUSTOMARY LAND BY PARTIES OUTSIDE THE ENDE LIO CUSTOMARY LEGAL COMMUNITY IN ENDE REGENCY, EAST NUSA TENGGARA PROVINCE (Case Study of Supreme Court Decision No. 241 K/Pdt/2020) - Panggabean, Mora H Ramadhan; Sembiring, Rosnidar; Maria, Maria (NOMOI Law Review, 2025)
This research examines the vital role of customary land for the Ende Lio indigenous community in Ende Regency, East Nusa Tenggara as a cultural identity and source of livelihood passed down through generations, yet facing challenges in the form of land tenure disputes by external parties as seen in the Supreme Court Decision Number 241 K/Pdt/2020. Using normative juridical research methods with descriptive characteristics and qualitative analysis through literature study, the research finds that legal regulations regarding customary land tenure in Indonesia are based on the 1945 Constitution Article 18B paragraph (2), Basic Agrarian Law Article 3, and ATR/BPN Ministerial Regulation No. 14/2024. The Ende Lio traditional leader (Mosalaki) holds multidimensional responsibilities and authority over Tana Nggoro, encompassing spiritual, legal, social, and ecological aspects as the highest guardian of ancestral land. Analysis of the Supreme Court Decision demonstrates prioritization of recognition and protection of Tana Nggoro land belonging to the Ende Lio indigenous community by affirming that the disputed object constitutes ancestral heritage land of the Plaintiffs as Mosalaki, and declaring that land possession by external parties without legal title and without approval from authorized customary leaders constitutes an unlawful act.